Uptake of Healthcare Insurance and Its Associated Factors among Patients Seeking Care at Moi Teaching and Referral Hospital, Eldoret - Ngetich, T. K.; Aruasa, W. K.; Too, R. K.; Newa, F. (African Journal of Education,Science and Technology (AJEST), 2021)
Arising from the global practice and WHO recommendations, extending access to health care to all segments of the population, including the poor is an important objective of the Kenyan Government’s National Health-Sector Strategic Plan and National Development Agenda as outlined in the Kenya Vision 2030 policy framework (Ministry of Health, 2015). Health insurance is deemed as a means of protecting individuals from incurring high costs at times of illness. It is a potential mechanism for overcoming existing health inequities with consequent effort to promote uptake among the citizens as a way of promoting healthcare. This study examined the factors associated with uptake of healthcare insurance among patients seeking care at Moi Teaching and Referral Hospital, Eldoret, Kenya. A descriptive cross sectional-survey design was adopted involving 234 in-patients and out-patients seeking care at Moi Teaching and Referral Hospital. Stratified and Systematic sampling techniques were applied. Data was collected using structured questionnaires, coded, cleaned and entered into STATA (version 13) for analysis. Descriptive statistics were generated and bivariate analysis to determine factors associated with healthcare insurance uptake were carried out using OR and the Chi-square test. A multiple-logistic model was fitted to adjust for relationships. The study found out that uptake of healthcare insurance cover was a significantly associated with education level, marital status, income of the patients and level of awareness. Uptake of healthcare insurance cover was high among the old (Median = 35, IQR 29, 42) compared to the young (Median = 32, IQR 24, 40), p=0.013. Awareness about of healthcare insurance was associated with, p<0.001, while gender disparity did not show any differentials in uptake, p=0.163. The study concluded that males and the elderly were more likely to be enrolled in healthcare insurance schemes than females and the young. In addition, marital status and education level of an individual positively influenced uptake of healthcare insurance. However, the association between gender and healthcare insurance was not significant. The study further concluded that respondents with higher incomes had a higher likelihood of enrolling in a healthcare insurance scheme as compared to individuals with low income. Awareness about healthcare insurance schemes increased uptake of healthcare insurance. The study recommends the need to encourage women, the unmarried and the young to enroll in healthcare insurance schemes. In addition, insurance agents need to target people with low education levels to scale up uptake and further, healthcare insurance providers to tailor affordable products consistent with income differentials.